Identification of active substances for dually modulating the renin–angiotensin system in Bidens pilosa by liquid chromatography–mass spectrometry–based chemometrics. (March 2016) - Chen, Yan; Luo, Jianguang; Zhang, Qian; Kong, Lingyi
Highlights: Bio-assay guided exploration of fractions from Bidens pilosa using the renin- and ACE-inhibitory evaluations in vitro . The fractions were analyzed by LC–MS–based chemometrics analysis. Polyphenolics responsible for dually modulating the RAS were characterized by LC–Q-TOF–MS/MS. Abstract: Bidens pilosa is used as a functional food and a traditional Chinese medicine to treat hypertensive disease. In this study, based on a bioactivity-guided fractionation of renin- and angiotensin I-converting enzyme (ACE)-inhibitory activities, a method of liquid chromatography–mass spectrometry (LC–MS)-based chemometrics analysis was used to identify bioactive compounds from the ethanol extract of B. pilosa . Polyphenol-containing fraction exhibited the highest dual inhibitions towards renin and ACE activities. A total 18 marker metabolites were positively or tentatively identified by LC–MS/MS, five of which contributed most to distinguishing between active and inactive portions and were confirmed to possess in vitro dual inhibitory activities against renin and ACE. This is the first study to demonstrate the active constituents of B. pilosa for dually regulating the renin–angiotensin system (RAS) in vitro . This established method represents a rapid and effective method for the identification of bioactive compounds from functional foods and nutraceuticals.